Performance Measurement of Sharia Commercial Banks through Islamicity Performance Index and Sharia Maqashid Index - Marwal, M. Rafid (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
Calculation of financial ratios is carried out to show the quality of the banks’ financial performance. The objective of this research was to analyze the performance of Islamic commercial banks based on the Islamicity performance index and Maqashid sharia. The research method used was a mixed-method, which combined quantitative and qualitative methods with the research object of Islamic commercial banks registered at the financial services authority. The sampling technique used purposive sampling, with a total of six samples. The results showed that based on the Islamic performance index, BNI Syariah and BRI Syariah had good performance, while Bank Mandiri Syariah, Bank Panin Dubai Syariah, Bank Muamalat Indonesia and BCA Syariah had very good performance; maqashid sharia index, Bank BNI Syariah, BRI Syariah, Bank Mandiri Syariah and Bank Panin Dubai Syariah had good performance, while Bank Muamalat Indonesia and BCA Syariah had very good performance; islamicity performance index and maqashid sharia index, Bank BNI Syariah, BRI Syariah, Bank Mandiri Syariah and Bank Panin Dubai Syariah had good performance while Bank Muamalat Indonesia and BCA Syariah had very good performance.